ANALISIS TINGKAT KEPATUHAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) (STUDI KASUS DESA LONAM KABUPATEN SAMBAS) - Eko Febri Lusiono; Suharman Suharman (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2018)
This research entitled "Analysis of Community Compliance Level in Paying Land and Building Taxes (UN) Case Study of Lonam Village District of Sambas Regency" is a fundamental research considering that the transition of UN status which was originally a central tax has now become a regional tax. UN acceptance is very instrumental in regional development. The object in this study is the United Nations taxpayer and government officials who are authorized to collect the United Nations tax. The purpose of this research is to find out the community's compliance in paying land and building tax as an effort to increase the regional income in Lonam village. factors that influence community compliance in paying Land and Building Taxes as an effort to increase Regional Income in Lonam village, Subdistrict subdistrict. The research method used qualitative research, which is a research process that produces descriptive data the form of written or oral information obtained from the research object. This research is expected to be a benchmark for the government, whether taxpayers have complied with paying the UN and whether the community already knows the rules that are set because this research can be used as supporting media in the implementation of government regulations, especially the Regional Regulation. Sambas Number 6 of 2012 concerning Land and Rural and Urban Building Taxes.